The Fractional Carleson Measures on the Unit Ball of ℝn+1 - Dongfang Wang; Bolin Ma (Journal of Function Spaces and Applications)
We construct a quantity in terms of Lp integral of the Jacobian of a conformal self-map on the unit ball of ℝn+1. Then, we characterize the fractional Carleson measures on the unit ball by the quantity.